Shaping nursing profession regulation through history – a systematic review. (23rd March 2018) - Stievano, A.; Caruso, R.; Pittella, F.; Shaffer, F.A.; Rocco, G.; Fairman, J.
Abstract : Aim: The aim of this systematic review was to provide a critical synthesis of the factors that historically shaped the advancements of nursing regulators worldwide. Background: An in‐depth examination of the different factors that moulded regulatory changes over time is pivotal to comprehend current issues in nursing. Introduction: In the light of global health scenarios, the researchers explored the factors that historically influenced the socio‐contextual circumstances upon which governments made regulatory changes. Methods: A systematic search was performed on the following databases: PubMed, CINAHL, Scopus, OpenGrey and ScienceDirect. The review included papers from January 2000 to October 2016 published in English. The authors used the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) and an inductive thematic approach for synthesis. Results: Two main themes were identified: factors underpinning current challenges and historical and contextual triggers of regulation. The first theme was composed of three aspects: education, migration and internationalization, and policy and regulation; the second theme consisted of four attributes: demographics, economics, history of registration and wars, and historical changes in nursing practice. Discussion: Factors that shaped nursing regulation were linked to changing demographics and economics, education, history of nursing registration, shifting patterns of migration and internationalization, nursing practice, policy and regulation and significant societal turns often prompted by wars. Conclusion: A deeper understanding of the developments of the nursing regulatory institutions provides the foundation for portable standards that can be applied across an array of jurisdictions to guarantee a better public safety. Implication for nursing and health policy: Understanding factors that socially, legislatively and politically have influenced the development of regulatory bodies over time helps to mould local, national and international policies that have a stronger impact on health worldwide. To achieve this, there must be effective cooperation among systems of nursing regulations globally.